A fully coupled hydro-thermo-poro-mechanical model for black oil reservoir simulation - Pao, William K. S. (John Wiley & Sons, 2001)
Afully coupled formulation of a hydro-thermo-poro-mechanical model for a three-phase black oil reservoir model is presented. The model is based upon the approach proposed by one of the authors which fully couples geomechanical e!ects to multiphase #ow. Their work is extended here to include non-isothermal e!ects. The gas phase contribution to the energy equation has been neglected based on a set of assumptions. The coupled formulation given herein di!ers in several ways when compared to the earlier work and an attempt is made to link the #ow based formulation and mixture theory. The Finite Element Method is employed for the numerical treatment and essential algorithmic implementation is discussed. Numerical examples are presented to provide further understanding of the current methodology.